2010
DOI: 10.1002/jsfa.3965
|View full text |Cite
|
Sign up to set email alerts
|

A survey of ochratoxin A contamination in feeds and sera from organic and standard swine farms in northwest Italy

Abstract: None of the feed samples contained more than the maximum level (50 microg OTA kg(-1), considering a feed moisture content of 120 g kg(-1)) recommended by the European Commission for OTA in complementary and complete swine feedstuffs. The OTA contamination of organic feed and serum samples was found to be significantly higher than that of conventional feed and serum samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…Serum levels of OTA found in horses were similar to those found by other authors in swine (mean levels of 250–640 pg/mL) [19,20] but higher than those observed in chickens (mean levels of 13 pg/mL) [21]. Differences in OTA serum levels between animal species may well be related to the different half-lives of the toxin, which are strictly dependent on the affinity of its binding to serum proteins (retarding elimination and renal filtration) and to entero-hepatic circulation and biliary excretion, which might be responsible for toxin accumulation and prolonged elimination from the body [1,16,22].…”
Section: Resultssupporting
confidence: 88%
“…Serum levels of OTA found in horses were similar to those found by other authors in swine (mean levels of 250–640 pg/mL) [19,20] but higher than those observed in chickens (mean levels of 13 pg/mL) [21]. Differences in OTA serum levels between animal species may well be related to the different half-lives of the toxin, which are strictly dependent on the affinity of its binding to serum proteins (retarding elimination and renal filtration) and to entero-hepatic circulation and biliary excretion, which might be responsible for toxin accumulation and prolonged elimination from the body [1,16,22].…”
Section: Resultssupporting
confidence: 88%
“…Ochratoxin A extraction from serum and from kidney and liver samples was carried out according to the methods developed by Pozzo et al. () and Vettorazzi et al. (), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…), and other animal‐derived swine products (Pozzo et al . ). In aquaculture species, the fact that OTA may cause severe degeneration and necrosis of kidney and liver leading to inferior weight gains, poorer feed conversion rate, lower survival and haematocrit (Doster et al .…”
Section: Mycotoxins In Aquafeedmentioning
confidence: 97%